Non-traditional cytokines: How catecholamines and adipokines influence macrophages in immunity, metabolism and the central nervous system. Issue 2 (April 2015) - Barnes, Mark A.; Carson, Monica J.; Nair, Meera G.
Highlights Macrophages modulate immunity in response to, and by producing, catecholamines. Adipokines influence metabolic outcomes by modulating macrophage phenotype. RELM proteins promote adverse metabolic outcomes such as lipid accumulation. RELM proteins can both promote and decrease susceptibility to infection.